La médiation numérique du patrimoine : quels savoirs au musée ? - Patrick Fraysse (Centre National d'Enseignement à Distance, 2015)
Our researches on the innovative cultural mediations to the museum take part in current reflection in Information and communication Sciences (SIC) on cultural mediation and its diverse typologies; we wish to enrich the definition of this process, by focusing on the increasing number of digital devices in museums today. Behind the deceptively obvious fact of a generalized mediation, the computing devices, whether networks or digital devices of cultural mediation, question the practices of the users, the visitors in museums, while blurring the borders between digitalization and access to collections, real heritage and digital heritage, transmission / valuation and appropriation / division. The survey led to the identification of digital devices wavering between information, mediation and communication. The interviews with the heads of two educational departments in two museums in Toulouse, raise the question of the knowledge offered by museums: scientific knowledge stemming from the study of objects, technical knowledge conveyed by the mediating objects or the devices, and the empirical knowledge of the public.